In-depth insights of inhibitory behaviour of 2-amino-4-methylthiazole towards galvanised steel in neutral NaCl solution. (1st May 2022) - Deng, Qiushi; Jeschke, Steffen; Murdoch, Billy J.; Hirth, Sabine; Eiden, Philipp; Gorges, Jan N.; Keil, Patrick; Chen, Xiao-Bo; Cole, Ivan
Abstract: Inhibitory behaviour of 2-amino-4-methyl-thiazole (2AT-Me) towards electro-galvanised steel (ZE) was investigated in neutral NaCl solution by electrochemical and surface analyses. It revealed that 2AT-Me acts as a mixed-type inhibitor with pronounced inhibition efficiency above 90% at a concentration of 15 mM. The adsorption behaviour of 2AT-Me upon ZE surface aligns with the Temkin adsorption isotherm. Moreover, surface studies illustrated that the formed protective film exhibits a multi-layered spatial structure comprising of passive oxides and inhibitor layers. The findings show promises for deploying small thiazole-based compounds in corrosion inhibition of ZE and zinc surfaces. Graphical Abstract: ga1 Highlights: 2-amino-4-methylthiazole (2AT-Me) behaves as a competent corrosion inhibitor for galvanised steel in NaCl solution. The adsorption process follows the Temkin adsorption isotherm, with the determined Δ G 0 ads of − 37.2 kJ mol −1 . A multi-layer structure of surface film was identified composing of both metal oxides and adsorbed inhibitor molecules. The multi-layer structured film mitigates corrosion kinetics of underlying galvanised steel in NaCl solution.